Fiber photometry for monitoring cerebral oxygen saturation in freely-moving rodents - Yu, Linhui (Biomed Opt Express, 2020)
Hemodynamic parameters, such as tissue oxygen saturation and blood volume fraction, are important markers of brain physiology. They are also widely used surrogate markers of electrophysiological activity. Here, we present a single fiber spectroscopic (SFS) system for monitoring cerebral oxygen saturation in localized, non-line-of-sight brain regions in freely-moving rodents. We adapted the implantation ferrule and patch cable design from commercialized optogenetics and fiber photometry systems, enabling stereotaxic fiber implantation, longitudinal tissue access and measurement from freely-moving animals. The optical system delivers and collects light from the brain through a 200 µm-core-diameter, 0.39NA multimode fiber. We robustly measured oxygen saturation from phantoms with different optical properties mimicking brain tissue. In mice, we demonstrated, for the first time, measurements of oxygen saturation from a highly-localized, targeted brain region over 31 days and continuous measurements from a freely-moving animal for over an hour. These results suggest that single fiber spectroscopy has enormous potential for functional brain monitoring and investigating neurovascular coupling in freely-moving animals. In addition, this technique can potentially be combined with fiber photometry systems to correct for hemodynamic artifacts in the fluorescence detection.